The Chemistry of Imaging Probes (2018)
Molecular imaging consists of the “in vivo characterization and measurement of biologic processes at the cellular and molecular level”. Any molecular imaging procedure requires an imaging probe that is an agent used to visualize, characterize and quantify biological processes in living systems and is specific for a given molecular event. Therefore, chemistry plays a vital role in the development of this cutting-edge methodology. This Research Topic aims at showing how chemistry can offer molecular imaging the opportunity to express all its potential. In fact, the most challenging problems of molecular imaging can be addressed by exploiting the outstanding possibilities offered by modern synthetic organic and coordination chemistry and the efficient procedures provided by conjugation chemistry. The optimization of innovative imaging probes can be pursued through different approaches: from the design of imaging units endowed with enhanced sensitivity to the control of the structural and electronic determinants responsible for the molecular recognition of the target molecule. A molecular imaging probe typically consists of an agent that usually produces signal for imaging purpose (often made of a metal complex), a targeting moiety, and a linker connecting the targeting moiety and the signaling agent. Currently, the diagnostic imaging modalities include Computed Tomography (CT), Magnetic Resonance Imaging (MRI), Ultrasound (US), Nuclear Imaging (PET, SPECT) and Photoacoustic Imaging (PAI). The basis for designing imaging probes for a given application is dictated by the chosen imaging modality, which in turn is dependent upon the concentration and localization profile (vascular, extracellular matrix, cell membrane, intracellular, near or at the cell nucleus) of the target molecule. The development of high-affinity ligands and their conjugation to the targeting vector is one of the key-steps for pursuing efficient molecular imaging probes. Importantly, in case of metal-based imaging reporters, the observation of toxic effects related to fast release of the metal ion from the corresponding complex prompted research efforts aimed at the enhancement of both the thermodynamic and kinetic stability of the chelates, via the fine tuning of the physico-chemical properties characterizing the chelating agents. We encourage papers focused on the design and synthesis of innovative imaging probes for any imaging modality, on the study on toxicity and stability of the metal-based probes and on in vitro and in vivo testing of new imaging probes for application in oncology, inflammation infection, cardio imaging, neuroinflammation and neuro-oncology.